Soluble Flavanthrone Derivatives: Synthesis, Characterization, and Application to Organic Light‐Emitting Diodes. Issue 23 (23rd April 2016) - Kotwica, Kamil; Bujak, Piotr; Data, Przemyslaw; Krzywiec, Wojciech; Wamil, Damian; Gunka, Piotr A.; Skorka, Lukasz; Jaroch, Tomasz; Nowakowski, Robert; Pron, Adam; Monkman, Andrew
Abstract: Simple modification of benzo[ h ]benz[5, 6]acridino[2, 1, 9, 8‐ klmna ]acridine‐8, 16‐dione, an old and almost‐forgotten vat dye, by reduction of its carbonyl groups and subsequent O ‐alkylation, yields solution‐processable, electroactive, conjugated compounds of the periazaacene type, suitable for the use in organic electronics. Their electrochemically determined ionization potential and electron affinity of about 5.2 and −3.2 eV, respectively, are essentially independent of the length of the alkoxyl substituent and in good agreement with DFT calculations. The crystal structure of 8, 16‐dioctyloxybenzo[ h ]benz[5, 6]acridino[2, 1, 9, 8‐ klmna ]acridine (FC‐8 ), the most promising compound, was solved. It crystallizes in space group P 1 ‾ and forms π‐stacked columns held together in the 3D structure by dispersion forces, mainly between interdigitated alkyl chains. Molecules ofFC‐8 have a strong tendency to self‐organize in monolayers deposited on a highly oriented pyrolytic graphite surface, as observed by STM. 8, 16‐Dialkoxybenzo[ h ]benz[5, 6]acridino[2, 1, 9, 8‐ klmna ]acridines are highly luminescent, and all have photoluminescence quantum yields of about 80 %. They show efficient electroluminescence, and can be used as guest molecules with a 4, 4′‐bis( N ‐carbazolyl)‐1, 1′‐biphenyl host in guest/host‐type organic light‐emitting diodes. The best fabricated diodes showed a luminance of about 1900 cd m −12, a luminance efficiency of about 3 cd A −1, and external quantum efficiencies exceeding 0.9 %. Abstract : New life for an old dye : Simple modification of flavanthrone, an old, intractable, and almost‐forgotten vat dye, by reduction of its carbonyl groups to phenolates followed by O ‐alkylation, gave a new group of solution‐processable, electroactive, conjugated compounds (see figure). Their HOMO and LUMO energies, as well as their ionization potentials and electron affinities, make them suitable for application as components of organic light‐emitting diodes.